Determination of atenolol in pharmaceutical formulations by diffuse reflectance spectroscopy - Gotardo, M. A. [UNESP]; Sequinel, R. [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (FapUNIFESP (SciELO), 2008)
A simple analytical method for quantification of atenolol in pharmaceutical formulations by diffuse reflectance spectroscopy is described. The method is based on the reaction, on the filter paper surface, between the drug and p-chloranil producing a colored compound. The best reaction conditions were obtained with 20 μL of atenolol solution and 20 μL of p-chloranil. All reflectance measurements were carried out at 550 nm and the linear range was from 1.13×10-2 to 7.88×10-2 mol L-1 (r = 0.9992). The limit of detection was 2.80 × 10-3 mol L-1. The proposed method was successfully applied to analysis of different commercial brands of pharmaceutical formulations and the results obtained by the proposed method were in good agreement with those obtained using the British Pharmacopoeia method.
Keywords: Atenolol; Diffuse reflectance spectroscopy; p-chloranil, pharmaceutical formulations